Evaluation of diverse germplasm lines/cultivars for yield and yield components in blackgram (Phaseolus mungo) - SHARMA, B L; SINGH, D P; SINGH, K H (The Indian Journal of Agricultural Sciences, 2013)
A study was conducted during 1993-95 on the extent of variability in 87 and 30 lines/cultivars in the blackgram(Phaseolus mungo L.). Based on the performance in 1993,5 surperior lines for each character as well as for yield /plantwere selected for the evaluation in 1995. Large extent of variability was observed for all the characters in both the yearsexcept for days to maturity. Some of the lines/cultivars were superior to the check (s) for different character (s). Whereas'HPU 4' was better than the best check,ie 'Pant U 19' in the replicated yield trial. Thirty lines/cultivars were representedby 4 distinct morphological groups.